Peran Guru dalam Proses Pembelajaran Siswa Anak Berkebutuhan Khusus di UPTD SDN Keleyan 1 - 'Aqiilah, Salsabil; Estu Harsiwi, Nova (ALENA : Journal of Elementary Education, 2024)
Teachers as education providers have an important role in developing the potential and abilities of students in order to make them become figures for their lives. This is what makes the researcher to discuss the role of teachers in the learning process, especially for children with special needs. Through the results of interviews conducted by researchers at UPTD SDN Keleyan 1, it is known that there are children with special needs who are included in the category of slow learner type children with special needs. The research method used is a qualitative research method with data analysis techniques through three stages, namely organizing, synthesizing, and identifying. Data collection was carried out in addition to literature, researchers conducted interviews and observations. The results of the study obtained were that teachers play a role in the learning process by giving special attention, managing strategies and materials that are differentiated between regular children and children with special needs, creating a comfortable classroom atmosphere, conducting repeated and consistent exercises, and using learning media.